2016
DOI: 10.1007/s00262-016-1939-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective effect of cytokine-induced killer cells on survival of patients with early-stage melanoma

Abstract: Adoptive immunotherapy using cytokine-induced killer (CIK) cells has shown potential antitumor ability against several kinds of cancers, including melanoma. However, little is known about the achievable outcome of CIK cells in melanoma patients at different pathological stages. Here we recruited 55 patients treated with conventional therapy plus CIK cells as the CIK group, and 49 patients treated with conventional therapy alone as the control group. The pathological characteristics were comparable between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…We observed that CIK cell treatment prolonged the OS of patients with TNBC who were in stages N1, N2, and N3, although this result was not observed for patients with stage N0, I, IIA, IIB, or III disease [ 25 26 ]. In our study, we found that the patients in the early stages received the greatest benefit from CIK cell immunotherapy, and this result is consistent with some previous studies [ 27 28 ]. This may indicate that the immune function of patients with advancedstage TNBC is suppressed and that a high tumor burden influences the therapeutic effects of CIK cells [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that CIK cell treatment prolonged the OS of patients with TNBC who were in stages N1, N2, and N3, although this result was not observed for patients with stage N0, I, IIA, IIB, or III disease [ 25 26 ]. In our study, we found that the patients in the early stages received the greatest benefit from CIK cell immunotherapy, and this result is consistent with some previous studies [ 27 28 ]. This may indicate that the immune function of patients with advancedstage TNBC is suppressed and that a high tumor burden influences the therapeutic effects of CIK cells [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found that CIK treatment combined with chemotherapy could effectively reduce the recurrence and metastasis in TNBC patients, thereby prolonging overall survival, and it had a stronger effect on patients at relatively early-stage of the disease. The conclusion that the patients in the early stages are the ones most benefited from CIK treatment was in line with some of the results from available studies on the treatment of other early-stage tumors by CIK immune cells 26, 27 . Several mechanisms could further contribute to the observed phenomenon.…”
Section: Discussionsupporting
confidence: 81%
“…The hypothesis of the protein serum effect on cultured CIK cells was followed by Guo et al [30], Meng et al [21], and Li et al [37]. On the contrary, Niam et al [31] used a complete nutrient medium of RPMI-1640 and 10% fetal calf serum, claiming that this was the optimal medium for CIK cell expansion, better than other serum-free MNCs culture media, despite that, the CD3 + CD56 + effective subset reported comprised a median of 26.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [30], who cultured CIK cells from healthy volunteers' blood donors for 14 days, reported CD3 + CD56 + proportion on day 14 as 25.31 ± 7.42%. Li et al [37], who cultured CIK cells from patients with early-stage melanoma blood for 14 days, reported CD3 + CD56 + proportion on day 14 as 21.8 ± 8%. On the other hand, these results did not go in line with Bonanno et al [46], who cultured PBMCs with different concentrations of anti-CD3 antibody (50,250, and 250 ng/mL) reported that the proportion of CD3 + CD56 + subsets on day 21 were 69.6%, 47.9%, and 29.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%